Modelling and Simulation of Rotary Dryer for Wheat drying - Goyal, Ankit; Bushra , Aishatul (Journal of Postharvest Technology, 2018)
Drying of the agricultural product has been one of most effective methods to reduce postharvest losses. Different studies are conducted to evaluate the performance of a rotary drier for drying of agricultural products. Rotary dryer is capable of processing a variety of agricultural product with a large number of thermo-physical and flow properties. Rotary dryers are used for drying of grains, beans, nuts, vegetables, herbs, woody biomass, animal feeds, agricultural wastes, and by-products. During this paper, a dynamic model to simulate the dehydration process of wheat in a rotary dryer is proposed. The results are validated with the experimental data obtained. The model predicts air and product moisture and temperature depending on operating conditions of the rotary dryer.